The effects of cold region meteorology and specific environment on the number of hospital admissions for chronic kidney disease: An investigate with a distributed lag nonlinear model - Wei Xinrui; Jiang Rui; Liu Yue; Zhao Guangna; Li Youyuan; Wang Yongchen (Frigid Zone Medicine)
To explore the effects of daily mean temperature (°C), average daily air pressure (hPa), humidity (%), wind speed (m/s), particulate matter (PM) 2.5 (μg/m3) and PM10 (μg/m3) on the admission rate of chronic kidney disease (CKD) patients admitted to the Second Affiliated Hospital of Harbin Medical University in Harbin and to identify the indexes and lag days that impose the most critical influence.